Current Status of Accountability of Local Bodies: A Concern of Development Studies (Journal of Tikapur Multiple Campus, 2014)
Local democracy is the foundation or cornerstone of democratic system. Accountability begins from the family. Accountability is the virtue of duty that denotes honesty and responsible undertakings. Accountability is an explanation of one's actions. The Government of Nepal (GoN) and the development partners (DPs) are active and seriously involved in creating conducive environment for social accountability in local governance within Nepal. In the long absence (almost 12 years) of elected representatives in the Local Bodies (LBs), Local governance and community development program (LGCDP) and subsequent program such as LGAF have proven to be effective means for maintaining local accountability at the local governments' levels. Mass media and civil society organizations (CSOs) have been effective instruments/tools to track out the social accountability as enshrined in the policy documents of the government. Nepal is at the transition of a new governance structure-unitary to federal, monarchy to republic set up and pluralism have more ups and downs over the years for charting out a new constitution from Constituent Assembly-II elections. The current government, both at the local as well as centre, have to discharge dual roles as: popular representatives and bureaucratic roles.